Determinants of the variability of heart rate measures during a competitive period in young soccer players - Buchheit, M.; Mendez-Villanueva, A.; Quod, M. J.; Poulos, N.; Bourdon, P. (European Journal of Applied Physiology, 2010)
Measurements of exercise heart rate (HRex), HR recovery (HRR) and HR variability (HRV) are used as indices of training status. However, the day-to-day variability of these indices throughout a competitive soccer period is unknown. On 14 occasions during a 3-week competition camp, 18 under 15 (U15) and 15 under 17 (U17) years soccer players performed a 5-min submaximal run, followed by a seated 5-min recovery period. HRex was determined during the last 30 s of exercise, while HRR and HRV were measured during the first and last 3 min of the post-exercise recovery period, respectively. U15 players displayed greater HRex (P = 0.02) and HRR (P = 0.004) compared with the U17 players, but there was no difference in HRV (P = 0.74). The mean coefficient of variation (CV) for HRex was lower than that for HRV [3.4 (90% CL, 3.1, 3.7) vs. 10.7 (9.6, 11.9)%, P < 0.001]; both were lower than that for HRR [13.3 (12.2, 14.3)%, P < 0.01]. In contrast to HRex and HRR, the CV for HRV was correlated to maximal aerobic speed (r = -0.52, P = 0.002). There was no correlation between total activity time (training sessions + matches) and CV of any of the quantified variables. The variability of each of these measures and player fitness levels should be considered when interpreting changes in training status.